Commercializing Traditional Green Spaces: A Sustainability Analysis of Telajakan Transformations Along Karna Street Ubud Bali - Putra, I Dewa Gede; Setijanti, Purwanita; Dinapradipta, Asri (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2025)
This study explores the transformation of telajakan—traditional green buffer spaces in Bali—into commercial zones, analyzing the influence of economic, social, environmental, and cultural factors. Telajakan, once important for maintaining environmental quality and cultural values, is increasingly being converted into commercial spaces, particularly in tourism-heavy areas. The research was conducted among 44 business operators along Jalan Karna, Ubud, where telajakan spaces are being transformed into kiosks. Data were collected using a Likert scale survey to assess the impact of these factors. The regression analysis revealed that while cultural factors significantly resisted the transformation (p = 0.008), economic and social pressures, such as financial incentives and community influence, had a greater impact. Environmental factors were not significant. The negative relationship between cultural factors and commercialization suggests that, although respondents did consider cultural values, these considerations were ultimately overpowered by economic priorities or cultural values were adapted to accommodate commercial needs. This study provides empirical insights into how economic forces and social dynamics are driving the commercialization of Bali's traditional green spaces.